PREFERENSI KONSUMEN TERHADAP PEMBELIAN KERUPUK IKAN DI KOTA SINTANG - WAHYUNI, TRI; NURLIZA, NURLIZA; KURNIATI, DEWI (Jurnal Social Economic of Agriculture, 2017)
This study aims to determine consumer preferences of fish crackers product in Sintang city, and to determine which attributes are most considered by consumers.Attributes of the product that were analyzed in this study is the flavor, packaging, price, location, shape, color, and thickness. The sampling technique in this research is non probability sampling, by conducting interviews with 150 respondents which were analyzed using SPSS 17.0 software with conjoint method. From the seven attributes of fish crackers, the most preferable attributes as the consumer's consideration, sequentially are the price attributes, flavor, packaging, location of purchasing the fish crackers, fish crackers shapes, colors and the last one is the thickness of the fish crackers.